Multiphase Hybrid Electric Machines Applications for Electrified Powertrains - Al-Adsani, Ahmad S.; Beik, Omid.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2022)
This book provides an insight into the design, modeling, control, and application of multiphase hybrid permanent magnet machines for electrified powertrains in electric and hybrid electric vehicles. The authors present an overview of electric and hybrid electric vehicles, hybrid electric machine topologies, hybrid permanent magnet (HPM) machine design, multiphase hybrid machines, operation of multiphase generators in series hybrid electric vehicles (SHEV), and machine hardware build-up and testing. Readers will gain an understanding of multiphase machine configuration, their design, control, and recent applications, along with the benefits they provide, and learn general design steps, prototyping, and hardware build-up processes of multiphase electric machines. Multiphase Hybrid Electric Machines: Applications for Electrified Powertrains will be a valuable reference for undergraduate and graduate students, researchers, and practicing engineers, working on electric/hybrid electric vehicles, as well as electric machine applications in renewable energy systems specifically wind turbines, HVAC systems, robotics, and aerospace industry. Presents an overview of electrification in the automotive industry; Offers step-by-step design procedures for multiphase and hybrid electric machines; Provides examples, case studies, and real-world applications.
General Electric Machines Theory -- Review of Hybrid Electric Machine Topologies -- Hybrid Permanent Magnet (HPM) Machine Design -- Overview on Multiphase Hybrid Machines -- Overview of Electric and Hybrid Electric Vehicles -- Operation of Multiphase HPM Generator in Series Hybrid Electric Vehicles (SHEV) -- HPM Machine Hardware Build-up and Tests -- Case Studies and Applications -- References -- Appendices.
Keywords: Automotive engineering; Electrical engineering; Energy policy; Energy and state; Engines; Engineering design; Automotive Engineering; Electrical and Electronic Engineering; Energy Policy, Economics and Management; Engine Technology; Engineering Design; Electric machinery; Electric vehicles -- Power trains